Community Revival in the Wake of Disaster Lessons in Local Entrepreneurship - Storr, Virgil Henry; Haeffele-Balch, Stefanie; Grube, Laura E.; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2015)
Explores the role of entrepreneurs in bringing about community rebound after disasters, with particular attention to recovery efforts following Hurricane Katrina and Hurricane Sandy.
Keywords: Economic theory; Microeconomics; Macroeconomics; Development economics; Sociology; Environmental sociology; Economics; Development Economics; Sociology, general; Microeconomics; Economic Theory/Quantitative Economics/Mathematical Methods; Environmental Sociology; Macroeconomics/Monetary Economics//Financial Economics; Electronic books